Neuroprotective effect of angiotensin II receptor blockers on the risk of incident Alzheimer’s disease: A nationwide population-based cohort study - Lee, Hyun Woo; Kim, Seungyeon; Jo, Youngkwon; Kim, Youjin; Ye, Byoung Seok; Yu, Yun Mi (Frontiers in Aging Neuroscience, 2023)
Background Recent studies on renin-angiotensin system (RAS) inhibitors have reported a reduced risk of Alzheimer’s disease (AD). Nevertheless, the effect of RAS inhibitor type and blood–brain barrier (BBB) permeability on the risk of AD is still unknown. Objectives To assess the effects of RAS inhibitors on the risk of AD based on the type and BBB permeability and investigate the cumulative duration-response relationship. Methods This was a population-based retrospective cohort study using the Korean Health Insurance Review and Assessment database records from 2008 to 2019. The data of patients diagnosed with ischemic heart disease between January 2009 and June 2009 were identified for inclusion in the analyses. Propensity score matching was used to balance RAS inhibitor users with non-users. The association between the use of RAS inhibitors and incident AD was evaluated using a multivariate Cox proportional hazard regression model. The results are presented in adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs). Results Among the 57,420 matched individuals, 7,303 developed AD within the follow-up period. While the use of angiotensin-converting enzyme inhibitors (ACEIs) was not significantly associated with AD risk, the use of angiotensin II receptor blockers (ARBs) showed a significant association with reduced risk of incident AD (aHR = 0.94; 95% CI = 0.90–0.99). Furthermore, the use of BBB-crossing ARBs was associated with a lower risk of AD (aHR = 0.83; 95% CI = 0.78–0.88) with a cumulative duration-response relationship. A higher cumulative dose or duration of BBB-crossing ARBs was associated with a gradual decrease in AD risk (P for trend < 0.001). No significant association between the use of ACEIs and the risk of AD was observed regardless of BBB permeability. Conclusion Long-term use of BBB-crossing ARBs significantly reduced the risk of AD development. The finding may provide valuable insight into disease-modifying drug options for preventing AD in patients with cardiovascular diseases.